2018
DOI: 10.1371/journal.pone.0204820
|View full text |Cite|
|
Sign up to set email alerts
|

Potential use of text classification tools as signatures of suicidal behavior: A proof-of-concept study using Virginia Woolf’s personal writings

Abstract: BackgroundThe present study analyzes the feasibility of text classification to predict individual suicidal behavior. Entries from Virginia Woolf’s diaries and letters were used to assess whether a text classification algorithm could identify written patterns associated with suicide.MethodsThis is a text classification study. We compared 46 text entries from the two months before Virginia Woolf’s suicide with 54 texts randomly selected from Virginia Woolf’s work during other periods of her life. Letters and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…It is also worth mentioning that a recent text classification study used letters and diaries of Virginia Woolf to identify written patterns associated with suicide. 65 Authors found an AUC of 0.80 and a balanced accuracy of 80.45% by using Naïve-Bayes machine-learning algorithm.…”
Section: Prediction Of Poor Clinical Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also worth mentioning that a recent text classification study used letters and diaries of Virginia Woolf to identify written patterns associated with suicide. 65 Authors found an AUC of 0.80 and a balanced accuracy of 80.45% by using Naïve-Bayes machine-learning algorithm.…”
Section: Prediction Of Poor Clinical Outcomesmentioning
confidence: 98%
“…Other studies also predicted suicidality by using machine learning coupled with a combined genomic and clinical risk assessment approach and built models with an AUC of 0.98 and 0.82 in patients with BD. It is also worth mentioning that a recent text classification study used letters and diaries of Virginia Woolf to identify written patterns associated with suicide . Authors found an AUC of 0.80 and a balanced accuracy of 80.45% by using Naïve‐Bayes machine‐learning algorithm.…”
Section: How Will Machine Learning and Big Data Analytics Contribute mentioning
confidence: 99%
“…Beyond content analysis, word valence further indicates risk, with positively valenced words associated with a 30% reduced likelihood of suicide (McCoy et al, 2016). Moreover, the application of ML algorithms to patient writing patterns has been shown to predict a suicide attempt up to 2 months in advance, with an 80% accuracy rate (de Avila Berni et al, 2018); this may enable early identification of suicidality if applied to data sources that can be captured in real time such as social media and other personal text-based communications. NLP has also been applied to acoustic analysis of audio conversations to discriminate suicidal and non-suicidal individuals based on spoken language differences (Pestian et al, 2016).…”
Section: Role Of Ai In Suicide Risk Predictionmentioning
confidence: 99%
“…Meanwhile, Eichstaedt et al (2018) built a model with some linguistic predictors to identify depressed Facebook users, with a higher prediction accuracy (AUC = 0.72). In addition, de Ávila Berni et al (2018) developed a model to identify texts proposed by suicidal individuals based on the Naïve-Bayes machine-learning algorithm. The model achieved a higher performance, with an accuracy of 80%.…”
Section: Discussionmentioning
confidence: 99%